The relativistic jet of the γ-ray emitting narrow-line Seyfert 1 galaxy PKS J1222+0413. Issue 1 (2nd May 2019) - Kynoch, Daniel; Landt, Hermine; Ward, Martin J; Done, Chris; Boisson, Catherine; Baloković, Mislav; Angelakis, Emmanouil; Myserlis, Ioannis
ABSTRACT: We present a multifrequency study of PKS J1222+0413 (4C +04.42), currently the highest redshift γ-ray emitting narrow-line Seyfert 1 (γ-NLS1). We assemble a broad spectral energy distribution (SED) including previously unpublished datasets: X-ray data obtained with the NuSTAR and Neil Gehrels Swift observatories; near-infrared, optical, and UV spectroscopy obtained with VLT X-shooter; and multiband radio data from the Effelsberg telescope. These new observations are supplemented by archival data from the literature. We apply physical models to the broad-band SED, parametrizing the accretion flow and jet emission to investigate the disc–jet connection. PKS J1222+0413 has a much greater black hole mass than most other NLS1s, M BH ≈ 2 × 10 8  M$\odot$, similar to those found in flat spectrum radio quasars (FSRQs). Therefore this source provides insight into how the jets of γ-NLS1s relate to those of FSRQs.